Foliar and stem epidermal anatomy of the tribe Cynoglosseae (Boraginaceae) and their taxonomic significance. Issue 6 (25th February 2019) - Attar, Farideh; Esfandani‐Bozchaloyi, Somayeh; Mirtadzadini, Mansour; Ullah, Fazal; Zaman, Wajid
Abstract : Foliar and stem epidermal anatomical features of the tribe Cynoglosseae have been studied in detail for the taxonomic identification using light microscopy (LM) and scanning electron microscopic (SEM) techniques. A comparative study was conducted on different plant parts (leaf and stem epidermal anatomy) of 25 species belonging to eight genera of the tribe Cynoglosseae (Boraginaceae) collected from different phytogeographical regions of Iran for the first time. Different qualitative and quantitative characteristics were observed in detail using LM and SEM. Results showed that although generally the stem and leaf anatomical traits were similar, but some diagnostic features were examined for distinguishing the closely related genera in the tribe. The ratio of cortex/diameter of stem and phloem/xylem, the average row number of collenchyma, palisade and spongy cells, structure of trichomes, type of indumentum and palisade arrangement were found taxonomically important. The anatomical characters were statistically analyzed using cluster analysis and principal component analysis. The study found that stem and leaf eccentrics are variable in the genus but constant within species of the same genus. Most species had typical isobilateral leaves, but some showed an incipient dorsoventrally symmetry with a layer of abaxial palisade tissue. Eglandular trichomes were observed found in all the studied species, which were recognized based on structure and function. In present study some novel characters have been observed which are of great interest to the taxonomist for the correct identification some genera delimitations. The characters studied here are of less taxonomic value and delimitating at species level. Abstract : Foliar epidermal anatomy of the tribe Cynoglosseae (Boraginaceae). Delimitations of genera and species in the tribe based on anatomical characters. Taxonomical characteristics of stem and leaf epidermis.